Homelessness and COVID-19 in New Zealand: Challenges, Emergency Responses, and Implications for Disaster Risk Reduction - Le Dé, Loïc; Fraser, Anita; St Martin, Mathew (Elsevier, 2023)
People experiencing homelessness have traditionally received limited attention in disaster research and disaster risk reduction policy. The COVID-19 pandemic has shed light on the vulnerable conditions of urban homelessness during emergency with unprecedented response efforts. Focusing on Aotearoa New Zealand, this research analyses homeless people's experiences of the COVID-19 and examines the policies and actions developed by government agencies and local organisations. The study highlights that while the homeless did not perceive the virus as a threat the COVID-19 framework with border closures and lockdowns had direct impacts on their livelihoods. The emergency policies focused mainly on homeless who are rough sleepers with a strong emphasis on emergency shelters. The study finds that while effective in temporally housing the homeless, the emergency shelters were often inappropriate to cater for homeless needs and lacked long-term views to transit towards sustainable solutions to homelessness. We also point out issues linked to coordination across agencies, leadership and resources needed for both effective emergency management and disaster risk reduction.
Keywords: 4407 Policy and Administration; 4409 Social Work; 44 Human Society; Homelessness; Emergency Care; 11 Sustainable Cities and Communities; 1202 Building; 1205 Urban and Regional Planning; 1604 Human Geography; Urban & Regional Planning; 3304 Urban and regional planning; 4404 Development studies; 4406 Human geography